Education and cardiovascular diseases: a Mendelian randomization study - Liu, Wei; Lin, Quan; Fan, Zongjing; Cui, Jie; Wu, Yang (Frontiers in Cardiovascular Medicine, 2024)
Background: Observational studies have indicated a potential association between education and cardiovascular diseases (CVDs). However, uncertainties regarding the causal relationship persist. Therefore, this study aimed to investigate whether higher levels of education causally reduce the risks of CVDs. Methods: Employing a two-sample Mendelian randomization (MR) design, our study examined the relationship between education and ten different CVDs. Utilizing data from the IEU Open GWAS database, relevant single nucleotide polymorphisms (SNPs) were identified through stringent screening criteria. Causality was assessed using the inverse-variance weighted (IVW), ME-Egger regression, and weighted median methods. Sensitivity analyses, including heterogeneity and pleiotropy tests, were conducted to ensure the robustness of our findings. Results: Our study identified a genetic predisposition associated with an additional 3.6 years of education, which significantly reduced the risk of various CVDs. Specifically, this genetic factor was found to lower the risk of type 2 diabetes by 46.5%, coronary heart disease by 37.5%, ischemic stroke by 35.4%, cardiac-related mortality by 28.6%, heart failure by 28.2%, transient ischemic attack by 24%, atrial fibrillation by 15.2%, peripheral artery disease by 0.3%, and hypertension by 0.3%. However, no significant evidence revealed a causal relationship between education and pulmonary embolism. Conclusion: Our study provides robust evidence supporting the role of higher educational attainment in reducing the incidence of various cardiovascular diseases, including type 2 diabetes, coronary heart disease, ischemic stroke, cardiac-related mortality, heart failure, transient ischemic attack, atrial fibrillation, peripheral artery disease, and hypertension. However, the impact of education on pulmonary embolism remains inconclusive.